Schisandrin B Antagonizes Cardiotoxicity Induced by Pirarubicin by Inhibiting Mitochondrial Permeability Transition Pore (mPTP) Opening and Decreasing Cardiomyocyte Apoptosis - Shi, Hongwei; Tang, Heng; Ai, Wen; Zeng, Qingfu; Yang, Hong; Zhu, Fengqing; Wei, Yunjie; Feng, Rui; Wen, Li; Pu, Peng; He, Quan (Frontiers in Pharmacology, 2021)
Objective: Pirarubicin (THP), one of the anthracycline anticancer drugs, is widely used in the treatment of various cancers, but its cardiotoxicity cannot be ignored. Schisandrin B (SchB) has the ability to upregulate cellular antioxidant defense mechanism and promote mitochondrial function and antioxidant status. However, it has not been reported whether it can resist THP-induced cardiotoxicity. The aim of this study was to investigate the effect of SchB on THP cardiotoxicity and its mechanism. Methods: The rat model of cardiotoxicity induced by THP was established, and SchB treatment was performed at the same time. The changes of ECG, cardiac coefficient, and echocardiogram were observed. The changes of myocardial tissue morphology were observed by H&E staining. Apoptosis was detected by TUNEL. The levels of LDH, BNP, CK-MB, cTnT, SOD, and MDA in serum were measured to observe the heart damage and oxidative stress state of rats. The expression of cleaved-caspase 9, pro/cleaved-caspase 3, Bcl-2/Bax, and cytosol and mitochondrial Cyt C and Bax was evaluated by western blot. H9c2 cardiomyocytes were cocultured with THP, SchB, and mPTP inhibitor CsA to detect the production of ROS and verify the above signaling pathways. The opening of mPTP and mitochondrial swelling were detected by mPTP kit and purified mitochondrial swelling kit. Results: After 8 weeks, a series of cardiotoxicity manifestations were observed in THP rats. These adverse effects can be effectively alleviated by SchB treatment. Further studies showed that SchB had strong antioxidant and antiapoptotic abilities in THP cardiotoxicity. Conclusion: SchB has an obvious protective effect on THP-induced cardiotoxicity. The mechanism may be closely related to the protection of mitochondrial function, inhibition of mPTP opening, and alleviation of oxidative stress and apoptosis of cardiomyocytes.